2007
DOI: 10.1039/b706921a
|View full text |Cite
|
Sign up to set email alerts
|

13,15-N-Cycloimide derivatives of chlorin p6 with isonicotinyl substituent are photosensitizers targeted to lysosomes

Abstract: Four monocationic cycloimide derivatives of chlorin p(6) (CICD) were studied as photosensitizers and compared to a structurally similar neutral derivative. Cationic CICD are highly photostable (quantum yield of photobleaching is about 1 x 10(-5), generate singlet oxygen under irradiation (quantum yields are 0.3-0.45), can be involved in a photo-induced substrate-dependent generation of superoxide radicals, but do not produce OH . 17,18-delta-lacton 13(2)-(N-methylisonicotinylamido)-13,15-cycloimide mesochlorin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 45 publications
0
23
0
1
Order By: Relevance
“…Four monocationic cycloimide derivatives of chlorin p 6 (CICD) 31-34 ( Figure 11) having λ max in 699-734 nm range were developed by Nazarova et al in 2007 as PSs and their photodynamic efficacies were compared to a structurally similar neutral derivative. 168 The authors found that the cationic CICD are highly photostable, generate singlet oxygen under irradiation, and can be involved in a photo-induced substrate-dependent generation of superoxide radicals, but do not produce OH • . Two of them possess high cancer cell killing photodynamic activity, but provide no photo-induced bactericidal effect.…”
Section: Chlorophyll A-based Long Wavelength Cationic Chlorinsmentioning
confidence: 99%
“…Four monocationic cycloimide derivatives of chlorin p 6 (CICD) 31-34 ( Figure 11) having λ max in 699-734 nm range were developed by Nazarova et al in 2007 as PSs and their photodynamic efficacies were compared to a structurally similar neutral derivative. 168 The authors found that the cationic CICD are highly photostable, generate singlet oxygen under irradiation, and can be involved in a photo-induced substrate-dependent generation of superoxide radicals, but do not produce OH • . Two of them possess high cancer cell killing photodynamic activity, but provide no photo-induced bactericidal effect.…”
Section: Chlorophyll A-based Long Wavelength Cationic Chlorinsmentioning
confidence: 99%
“…It was shown that chlorins without exo-cycle (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) cause an active photosensitized lysis of erythrocytes regardless of the substituent's nature. The presence of exocycle (compounds 1-19) in the most cases leads to decrease in photohemolysis power and increase in its induction period.…”
Section: Discussionmentioning
confidence: 99%
“…These photosensitizers absorb in the 705-745 nm range, where human tissues are relatively transparent for the exciting light. Varying different substituents the CIC derivatives were found, which accumulated intensely (distribution ratio of 5-11) in cytoplasm of cancer cells in a lipid-bound monomeric photoactive form [12][13][14][15][16]. Hydrophobic substituents provided predominant accumulation of CICD in lipid droplets.…”
Section: B Study Of Photosensitizersmentioning
confidence: 99%
“…The CSI technique was successfully used in the studies of sulfonated phthalocyanines [9][10][11], cycloimide derivatives of chlorin p 6 (CIC) [12][13][14][15][16][17][18] and bacteriochlorin p (CIBC) [19]. It helped to clarify the fact that chelating with a metal atom was not essential for the efficiency of phthalocyanines in anticancer PDT [9].…”
Section: B Study Of Photosensitizersmentioning
confidence: 99%